Knockdown of JMJD1C, a target gene of hsa-miR-590-3p, inhibits mitochondrial dysfunction and oxidative stress in MPP+-treated MES23.5 and SH-SY5Y cells - Wang, J; Le, T; Wei, R; Jiao, Y (Cellular and Molecular Biology, 2016)
MicroRNAs have been shown to be closely related to many neurodegenerative disorders. The present study focuses on the role of hsa-miR-590-3p and its function in Parkinson's disease (PD). Our study showed a remarkable down-regulation of miR-590-3p expression in the 1-methyl-4 phenylpyridinium (MPP+)-treated MES23.5 and SH-SY5Y cells. Furthermore, JMJD1C was identified as a target gene of miR-590-3p in humans via the luciferase reporter assay. Our study also demonstrated that up-regulation of miR-590-3p and knockdown of JMJD1C increased the expression of peroxisome proliferator-activated receptor Î³ coactivator-1Î± (PGC-1Î±) and the downstream targets of PGC-1Î±, including nuclear respiratory factor 1 (NRF-1) and mitochondrial transcription factor A (TFAM), which are the key genes regulating mitochondrial function. Also, the expression of heme oxygenase-1 (HO-1), NAD (P) H quinone oxidoreductase-1 (NQO-1) and Î³-glutamylcysteine synthetase (Î³-GCS) involved in anti-oxidation was increased. Moreover, there was a significant increase in the total cellular ATP with an associated decrease in levels of ROS in the absence of JMJD1C. Taken together, these results show that miR-590-3p plays an important role in the pathogenesis of PD, which may be further regarded as a therapeutic target.